"Choosing the best policy for demand tracking strategy in aggregate planning" Case study in Diyala General Company for Electrical Industries / Power Transformers Factory - Haidar Shakir Nwry (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
Dealing with research and studies operations decisions according to the entrance of operations or strategic, in both cases subject to the accounts Quantitative affect the take, and through follow the situation of the reality of the aaggregate planning, particularly Chase demand strategy in the power transformer plant a Diyala Company for Electrical Industries factories sample of search, it was found that planning is based on personal experience and self-governance or used Aggregate Planning for the year earlier with some modifications, which may cause weakness in the ability to demand for transformers despite the availability of energy to meet orders. The aim of the research to identify the real situation of Aggregate Planning in the company In order to evaluation the best policy to meet market demand changes. and using software (Excel) as identified some of the mathematical equations used in calculate the costs of the policies that have been compared, which (Vary Work – Force, Over time or Idle time, Subcontracting, and Manipulating Inventory Levels) results have shown a preference to control the policy of operating in the aaggregate planning of the plant by force as shown less cost, and against which has been drafting a set of recommendations which will hopefully be taken advantage of stakeholders in the current research.